Prescription pattern for antivirals in the treatment of chronic hepatitis B: the EUPTHEA Study. Issue 3 (19th February 2013) - Requena, Teresa; Martín, Maria Teresa; Desongles, Trinidad; Castillo, Isabel; Lorente, Laura; Yébenes, Maria; ,
Abstract : Objective: To study and compare the prescription pattern for antivirals to treat chronic hepatitis B in Spain and its autonomous communities in 2009. Methods: Cross-sectional study, via hospital pharmacy services, of a non-co-infected adult population treated for hepatitis B infection in the previous 6 months. A Spanish Hospital Pharmacy Society website application was used for data collection. The statistical program PASW 18.0 was used to analyse data for Spain (percentage) and for its autonomous communities (percentage, autonomous community percentage range). Results: The study included 2614 patients from 34 hospitals in all the Spanish autonomous communities except the Canary Islands, La Rioja, Ceuta and Melilla. Over three-quarters (76.1%) of the patients received monotherapy, and the remainder received combination therapy; the equivalent percentage ranges for the autonomous communities were 57.0–79.8% and 20.2–43.0%, respectively. Use of the different antivirals (autonomous community percentage ranges in parentheses) was as follows: lamivudine, 34.8% (27.4–48.3%); entecavir, 25.8% (18.5–32.7%); adefovir dipivoxil, 21.0% (10.3–26.5%); tenofovir, 16.0% (5.9–21.4%); pegylated interferon α-2a, 1.7% (0.3–4.4%); and telbivudine, 0.8% (0.0–1.5%). The most commonly used combinations (autonomous community percentage ranges in parentheses) were as follows: lamivudine–adefovir dipivoxil, 60.4% (42.2–77.9%); lamivudine–tenofovir, 21.9% (6.5–35.2%); and entecavir–adefovir dipivoxil, 7.3% (0.0–14.8%). The monotherapy use profile for Castilla-Leon was different from those of the other autonomous communities. Conclusions: Monotherapy was the most commonly used treatment regimen for hepatitis B. Lamivudine was the most widely used drug for monotherapy, and lamivudine with adefovir dipivoxil was the most common combination.